A REVISION OF ISACHNE IN MALESIA 2: SECT. ALBENTES (GRAMINEAE, ISACHNEAE) - Veldkamp J.F. (REINWARDTIA, 2018)
VELDKAMP, J. F. 2018. A revision of Isachne in Malesia 2: Sect. Albentes (Gramineae, Isachneae). Reinwardtia 17 (1): 1–33. — There are 23 species of Isachne in Malesia of which the 16 belonging to sect. Albentes are revised here. Isachne fera (N. Sumatra) and I. glandulosa (W. Sumatra) are new species, and so is I. bsipiana from Vanuatu. Isachne clementis and I. vulcanica are distinct species. Isachne albomarginata and I. beneckei are reduced to I. clarkei, I. obtecta to I. stricta, I. repens to I. commelinifolia (which is reinstated here), I. saxicola to I. clementis. Isachne kunthiana restricted to Sri Lanka and S. India has been much misapplied to specimens of I.commelinifolia and I. schmidtii. Fifteen lectotypes are designated.